Bolivia: plural or multicultural State? The Case of a Plurinational State - Díaz-González, José Andrés (2017)
This essay reviews the process, and consequences of the declaration of Bolivia as a Plurinational State. Its main purpose is to determine if it responds to a model of Plural or Multicultural State. It development a review of the concepts of Pluralism, as coming from an individualistic tradition; and Multiculturalism, as coming from a community tradition. Based on the work carried out by various actors, as well as the review of some actions of the Bolivarian government, it is concluded that the 2009 Constitution installs a model of Plural State.